2011
DOI: 10.1007/s10509-011-0701-2
|View full text |Cite
|
Sign up to set email alerts
|

Using the CeSiC material for the WSO-UV spectrographs

Abstract: The World Space Observatory Ultraviolet (WSO-UV) is a multi-national project lead by the Russian Federal Space Agency (Roscosmos) with the objective of high performance observations in the ultraviolet range. The 1.7 m WSO-UV telescope is equipped with UV spectrographs (responsibility of Russia and Germany) and UV imagers (responsibility of Spain). The UV spectroscopic instrumentation comprises two high resolution echelle spectrographs operating in wavelength ranges of 102-176 nm and 174-310 nm respectively, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…COS is expected to continue remain in operation at least through 2016. In addition to the outstanding scientific return of the COS instrument, lessons learned from COS will benefit future UV space missions, such as the World Space Observatory FUV and NUV Spectrographs (Reutlinger et al 2011;Shustov et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…COS is expected to continue remain in operation at least through 2016. In addition to the outstanding scientific return of the COS instrument, lessons learned from COS will benefit future UV space missions, such as the World Space Observatory FUV and NUV Spectrographs (Reutlinger et al 2011;Shustov et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In this instrument was used MCP detector as well. CeSiC material was selected for the spectrograph construction (Reutlinger et al 2011). …”
Section: Wuvs Optical Schemementioning
confidence: 99%
“…CeSiC is a ceramic matrix composite that is characterized by high stiffness and mechanical strength, high thermal conductivity, low CTE, and quick, relatively inexpensive manufacturing time. These characteristics make CeSiC a suitable material at reasonable cost for high-precision space optical and structural applications although the practice of the phase-B study has demonstrated that the CeSiC technology requires additional studies to obtain the stable characteristics of this new prospective construction material (Reutlinger et al 2011). Such characteristics will make it possible to perform detailed spectral observations and analyses of objects up to V = 17 m (Klochkova et al 2009;Sachkov 2010).…”
Section: Wso-uv Science Instrumentsmentioning
confidence: 99%